2001
DOI: 10.1051/0004-6361:20000258
|View full text |Cite
|
Sign up to set email alerts
|

H2infrared emission and the formation of dense structures in the Orion molecular cloud

Abstract: Abstract.Observations are reported of IR emission of H2 from a region of the Orion molecular cloud (OMC1) between the Becklin-Neugebauer object and IRc2 to the north and the Trapezium stars to the south. Data were obtained using the ESO 3.6 m telescope in the K-band around 2 µm with the ADONIS adaptive optics system. Images of H2 v = 1−0 S(1) show a spatial resolution of ∼0.15 . Detailed investigations of the distribution of sizes of structures in our images have been performed by area-perimeter analysis, Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
62
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(70 citation statements)
references
References 49 publications
(61 reference statements)
7
62
1
Order By: Relevance
“…This scenery may find support in the observations of GG, who showed that the emission of the CO P (8) line is unevenly distributed around Peak 1, and in the NICMOS image of the region (Stolovy et al 1998), showing a smallscale clumpy structure in the emission of the H 2 v = 1−0 S(1) line. A clumpy structure has been also observed by Vannier et al (2001) around Peak 2. Second, the possibility that a substantial fraction of hydrogen is in atomic form cannot be disregarded (see RBD).…”
Section: The Derived Beam-averaged N (Co) Of ≈6×10mentioning
confidence: 68%
“…This scenery may find support in the observations of GG, who showed that the emission of the CO P (8) line is unevenly distributed around Peak 1, and in the NICMOS image of the region (Stolovy et al 1998), showing a smallscale clumpy structure in the emission of the H 2 v = 1−0 S(1) line. A clumpy structure has been also observed by Vannier et al (2001) around Peak 2. Second, the possibility that a substantial fraction of hydrogen is in atomic form cannot be disregarded (see RBD).…”
Section: The Derived Beam-averaged N (Co) Of ≈6×10mentioning
confidence: 68%
“…Molecular densities are derived from analyses of near-infrared excitation and extinction, as well as being inferred from flux levels. Derived molecular densities range from 10 4 cm −3 in outflows from lowmass protostars like HH 111 to above 10 6 cm −3 in the OMC-1 outflow (Nisini et al 2002a;Vannier et al 2001). The density is critical in determining the cooling length behind the shock and this, subsequently, controls the nature of the flow (Blondin et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Self-similarity and lack of characteristic scale in molecular clouds must however break down at some dimension or range of dimensions associated with star formation, as demonstrated in Vannier et al (2001) and Gustafsson et al (2006). Turbulence creates local clumps of gas and this process, known as turbulent fragmentation, is considered the root cause of observed density structure and may give rise to large density contrasts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, four different methods were used in Vannier et al (2001) in order to demonstrate that self-similarity breaks down at star-forming scales of around 500-1000 AU in a small portion of the Orion Molecular Cloud (OMC1). The present contribution should be seen in this light, not as a panacea for structure identification but rather as another tool for this purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation